Internet connectivity disruption in Montenegro (Montenegro) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Montenegro. Data sourced from IODA.
Network Disruption Incident ID: ME-2026-0016. Severity: critical. Confidence: 65%